2020
DOI: 10.1016/j.jmig.2019.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Outcomes of Non-robotic Single-incision Laparoscopic Sacrocolpopexy: A Surgical Technique

Abstract: Study Objective: Our main purpose was to describe the surgical technique and short-term outcomes of single-incision laparoscopic sacrocolpopexy (S-LSC) for the treatment of pelvic organ prolapse (POP). Design: This study consisted of a retrospective analysis of 49 consecutive cases. Setting: This study was set at the Third Affiliated Hospital of Guangzhou Medical University from October 2016 to November 2017. Patients: The population for this study consisted of women with stage II to IV POP who met eligibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Thirty-nine studies with 3,349 patients met inclusion criteria for the sacrocolpopexy category. Three compared both suture types, 9,39,40 and 36 used one suture type (20 permanent 41–60 and 16 absorbable 8,61–75 ); 2,045 patients underwent sacrocolpopexy with permanent suture, and 1,304 with absorbable suture. Overall, nine studies were RCTs, 12 were comparative (two prospective, nine retrospective, one unclear direction), and 18 were single-arm (six prospective, 12 retrospective).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-nine studies with 3,349 patients met inclusion criteria for the sacrocolpopexy category. Three compared both suture types, 9,39,40 and 36 used one suture type (20 permanent 41–60 and 16 absorbable 8,61–75 ); 2,045 patients underwent sacrocolpopexy with permanent suture, and 1,304 with absorbable suture. Overall, nine studies were RCTs, 12 were comparative (two prospective, nine retrospective, one unclear direction), and 18 were single-arm (six prospective, 12 retrospective).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous research, we reported that vNOTES-SC [ 5 , 26 ] and LESS-SC [ 6 ] had good short-term clinical efficacy after the operation; however, data analysis and comparison of the differences between the two techniques were not performed. Thus, further observation of the mid- and long-term follow-up outcomes was required.…”
Section: Discussionmentioning
confidence: 99%
“…Sacral hysteropexy was first reported as early as 1957 by Arthure et al [ 3 ], while Nezhat et al [ 4 ] published the first case of laparoscopic sacrocolpopexy (LSC) in 1994. Subsequently, surgical routes for sacrocolpopexy have diversified with the rapid development and extensive application of minimally invasive techniques, including LSC with or without robot assistance, transvaginal natural orifice transluminal endoscopic sacrocolpopexy (vNOTES-SC) [ 5 ], and laparoendoscopic single-site sacrocolpopexy (LESS-SC) [ 6 ]. Currently, only a few studies have investigated the clinical application and efficacy of vNOTES-SC and LESS-SC.…”
Section: Introductionmentioning
confidence: 99%